ROMANTISISME DAN INTUISIONISME - Heatubun, Fabianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2007)
Romantic heritage, as a philosophical current, is still central to our recent culture. The ecological issues and pluralism not only exist in the realm crucial problem of the weakness in political commitment, but first of all it is that of ethics and moral. Thus, it is the problem of inner voice, personal and spiritual. Romanticism disagree with rationalism and materialism  epistemology, subsequently, they look for 'philosophy of nature' as a source and their basic worldview. Prophetically speaking, the primacy of intuition, imagination, feeling and passion, as an aesthetics terminology, are the words which they strived to answer the problem. The wisdom of nature have teach our human beings. Back to 'noble savage' is an imperative action, because history has teach us.